Precipitous decline of white-lipped peccary populations in Mesoamerica. (February 2020) - Thornton, Daniel; Reyna, Rafael; Perera-Romero, Lucy; Radachowsky, Jeremy; Hidalgo-Mihart, Mircea G.; Garcia, Rony; McNab, Roan; Mcloughlin, Lee; Foster, Rebecca; Harmsen, Bart; Moreira-Ramírez, José F.; Diaz-Santos, Fabricio; et al.
Abstract: Large mammalian herbivores are experiencing population reductions and range declines. However, we lack regional knowledge of population status for many herbivores, particularly in developing countries. Addressing this knowledge gap is key to implementing tailored conservation strategies for species whose population declines are highly variable across their range. White-lipped peccaries ( Tayassu pecari ) are important ecosystem engineers in Neotropical forests and are highly sensitive to human disturbance. Despite maintaining a wide distributional range, white-lipped peccaries are experiencing substantial population declines in some portions of their range. We examined the regional distribution and population status of the species in Mesoamerica. We used a combination of techniques, including expert-based mapping and assessment of population status, and data-driven distribution modelling techniques to determine the status and range limits of white-lipped peccaries. Our analysis revealed declining and highly isolated populations of peccaries across Mesoamerica, with a range reduction of 87% from historic distribution and 63% from current IUCN range estimates for the region. White-lipped peccary distribution is affected by indices of human influence and forest cover, and more restricted than other sympatric large herbivores, with their largest populations confined to transboundary reserves. To conserve white-lipped peccaries in Mesoamerica, transboundary efforts will be needed that focus on both forest conservation and hunting management, increased cross-border coordination, and reconsideration of country and regional conservation priorities. Our methodology to detail regional white-lipped peccary status could be employed on other poorly-known large mammals.